TerraSAR-L Interferometric Cartwheel : DEM Performance Estimation - Amiot, Thierry; Krieger, Gerhard; Douchin, Fracoise; Werner, Marian; Fjortoft, Roger (Radar Conference, 2004)
This paper focuses on interferometric performance estimation for a TerraSAR-L cartwheel constellation. Assuming receiving antennas of only 3 m diameter, the ambiguity and timing analysis leading to the selection of some radar parameters is presented. The paper briefly introduces the approach to estimate the Digital Elevation Model (DEM) performance. This part includes a discussion of the ambiguity behaviour in interferometric products. Finally, the DEM accuracies are estimated for different across-track baselines and swaths. Impacting parameters, such local ground slope, volume decorrelation or signal bandwidth are also considered.
DLR Import::2019-04-03